A network-based pharmacological investigation to identify the mechanistic regulatory pathway of andrographolide against colorectal cancer - Janani, Balakarthikeyan; Vijayakumar, Mayakrishnan; Priya, Kannappan; Kim, Jin Hee; Geddawy, Ayman; Shahid, Mohammad; El-Bidawy, Mahmoud H.; Al-Ghamdi, Sameer; Alsaidan, Mohammed; Abdelzaher, Mohammad Hassan; Mohideen, Abubucker Peer; Ramesh, Thiyagarajan (Frontiers in Pharmacology, 2022)
Traditional cancer treatments have posed numerous obstacles, including toxicity, multiple drug resistance, and financial cost. On the contrary, bioactive phytochemicals used in complementary alternative medicine have recently increased attention due to their potential to modulate a wide range of molecular mechanisms with a less toxic effect. Therefore, we investigated the potential regulatory mechanisms of andrographolide to treat colorectal cancer (CRC) using a network pharmacology approach. Target genes of andrographolide were retrieved from public databases (PharmMapper, Swiss target prediction, Targetnet, STITCH, and SuperPred), while targets related to CRC were retrieved from disease databases (Genecards & DisGeNet) and expression datasets (GSE32323 and GSE8671) were retrieved from gene expression omnibus (GEO). Protein-protein interaction networks (PPI) were generated using STRING and Cytoscape, and hub genes were identified by topology analysis and MCODE. Annotation of target proteins was performed using Gene Ontology (GO) database DAVID and signaling pathway enrichment analysis using the Kyoto Encyclopedia and Genome Database (KEGG). Survival and molecular docking analysis for the hub genes revealed three genes (PDGFRA, PTGS2, and MMP9) were involved in the overall survival of CRC patients, and the top 3 genes with the lowest binding energy include PDGFRA, MET, and MAPK1. MET gene upregulation and PDGFRA & PTGS2 gene downregulation are associated with the survival of CRC patients, as revealed by box plots and correlation analysis. In conclusion, this study has provided the first scientific evidence to support the use of andrographolide to inhibit cellular proliferation, migration, and growth, and induce apoptosis by targeting the hub genes (PDGFRA, PTGS2, MMP9, MAPK1, and MET) involved in CRC migration and invasion.